Effects of traditional Chinese exercise on the treatment of COVID-19: A protocol for systematic review. Issue 8 (25th February 2022) - Chen, Li; Ji, Yu; Wang, QiPeng; Fu, MingFen
Abstract: Introduction: Since the end of December 2019, corona virus disease 2019 (COVID-19) has caused a huge impact in many countries and has attracted great attention from countries around the world. In fact, many studies have shown that during the fight against the COVID-19 epidemic. Chinese traditional exercise plays an active role in promoting human health. The main purpose of this study is to provide a reliable method and credible evidence to improve the prognosis of patients with COVID-19 through traditional Chinese exercise. Methods: This protocol is guided by the preferred reporting items for systematic reviews. By searching the following electronic databases: PubMed, EMBASE, MEDLINE, Cochrane Library, Web of Science, China National Knowledge Infrastructure Database, China Biomedical Literature Database, China Science, and Wan-Fang Database. The whole process includes selecting high-quality literature, extracting and analyzing, and assessing the risk of bias in order to summarize the therapeutic effect of traditional Chinese exercise on COVID-19 patients. Result: Research shows that prevention and treatment through traditional Chinese exercise can provide strong evidence against COVID-19. Conclusion: To provide a way to help prevent and treat COVID-19 through traditional Chinese exercise.